Merekonseptualisasi Kapasitas Analitis untuk Mengelola Sistem Pendidikan yang Kompleks: Mengintegrasikan Teori Kompleksitas dan Manajemen Pendidikan Berbasis Nilai Islam - Deny Haryadi; Murni Yanto; Muhammad Istan; Beni Azwar; Revi Permanasari; Hedi Herdiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to reconceptualize analytical capacity as a competency framework capable of supporting the management of complex education systems through the integration of complexity theory and Islamic values-based education management. The research method used was a systematic literature review, which examined reputable articles indexed in Scopus using structured identification, screening, eligibility assessment, and inclusion procedures. Data were analyzed through thematic and configurative synthesis to identify patterns, themes, and relationships between the complexity of education systems, analytical capacity, leadership, education policy, and Islamic education governance. The results indicate that analytical capacity can no longer be understood solely as the technical ability to read data, but rather as a structured competency framework encompassing critical thinking, data literacy, systems thinking, modeling, and decision-making in uncertain situations. The findings also indicate that analytical capacity can be systematically developed through contextual, collaborative, and reflective training. However, a research gap remains regarding the application of complexity theory in Islamic education management. The conclusion of this study confirms that the integration of complexity theory and Islamic value-based educational management can strengthen adaptive, ethical, and sustainable educational governance, making analytical capacity a crucial foundation for leadership and decision-making in navigating the increasingly complex dynamics of the education system. Keywords: Analytical Capacity, Educational Complexity, Islamic Educational Management